The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41467-023-42430-z
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection establishes a stable and age-independent CD8+ T cell response against a dominant nucleocapsid epitope using restricted T cell receptors

Cecily Choy,
Joseph Chen,
Jiangyuan Li
et al.

Abstract: The resolution of SARS-CoV-2 replication hinges on cell-mediated immunity, wherein CD8+ T cells play a vital role. Nonetheless, the characterization of the specificity and TCR composition of CD8+ T cells targeting non-spike protein of SARS-CoV-2 before and after infection remains incomplete. Here, we analyzed CD8+ T cells recognizing six epitopes from the SARS-CoV-2 nucleocapsid (N) protein and found that SARS-CoV-2 infection slightly increased the frequencies of N-recognizing CD8+ T cells but significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Nelson et al [ 53 ] found differences in N-specific T cells CD4+ between nonhospitalized and hospitalized individuals. In contrast, CD8+ T-cell responses to N differ according to severity but are not related to age [ 54 , 55 ]. Although T cells cannot neutralize viruses, they play a crucial role in preventing severe forms of infection.…”
Section: Immune Response Against the Nucleocapsid Proteinmentioning
confidence: 99%
“…Nelson et al [ 53 ] found differences in N-specific T cells CD4+ between nonhospitalized and hospitalized individuals. In contrast, CD8+ T-cell responses to N differ according to severity but are not related to age [ 54 , 55 ]. Although T cells cannot neutralize viruses, they play a crucial role in preventing severe forms of infection.…”
Section: Immune Response Against the Nucleocapsid Proteinmentioning
confidence: 99%